Vitamin D Deficiency in Turkish Women - Kıymet İkbal Karadavut; Aynur Başaran; Aytül Çakcı (Galenos Yayinevi, 2003)
Osteomalacia is a metabolic bone disease caused by deficiency of vitamin D or its active metabolites. Since poor exposure to sunlight is one of the most common causes of osteomalacia, the disease seems to be rare in countries receiving adequate sunlight. Although Turkey is receiving adequate sunlight throughout the year, Islamic dressing in some women might cause osteomalacia. We report 18 Turkish female patients with osteomalacia aged between 35-86 years. Most common presenting symptoms were bone aches or pains and muscle weakness. Diagnosis of osteomalacia was performed by determinations of low or low-normal serum and urinary calcium levels, decreased serum inorganic phosphorus and serum 25- hydroxyvitamin D levels, increased serum intact PTH and serum alkaline phosphatase levels. X-ray studies of the symptomatic sites were obtained. Radiographically generalized osteopenia was detected in all patients but, there were no pseudo-fractures. All patients were followed prospectively with the treatment of vitamin D analogues (1mg/day) and calcium supplements (1000mg/day). Response to treatment was evaluated with symptomatic relief and laboratory work-up. Criteria used to define clinical improvement include relief of pain, fatigue, muscle strength and weakness, and decrease in neurological complaints (including paresthesia, muscle spasms). Clinical response was observed in all patients after 2 months follow-up (mean duration 6 months). Most important risk factor common to all patients was excessive clothing due to religious teling. Excessive clothing might be a risk factor for osteomalacia in young to middle-aged and otherwise healthy women even in countries with adequate sunlight.